2023
DOI: 10.3390/biomimetics8020243
|View full text |Cite
|
Sign up to set email alerts
|

Vibration State Identification of Hydraulic Units Based on Improved Artificial Rabbits Optimization Algorithm

Abstract: To improve the identification accuracy of the vibration states of hydraulic units, an improved artificial rabbits optimization algorithm (IARO) adopting an adaptive weight adjustment strategy is developed for optimizing the support vector machine (SVM) to obtain an identification model, and the vibration signals with different states are classified and identified. The variational mode decomposition (VMD) method is used to decompose the vibration signals, and the multi-dimensional time-domain feature vectors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…For optimal selection of the features, the IARO algorithm is employed. The ARO technique [26] is presented based on the survival strategies followed by the rabbits. It involves three search strategies such as the detour foraging strategy, random hiding strategy, and energy shrink strategy.…”
Section: Feature Selection Using Iaro Algorithmmentioning
confidence: 99%
“…For optimal selection of the features, the IARO algorithm is employed. The ARO technique [26] is presented based on the survival strategies followed by the rabbits. It involves three search strategies such as the detour foraging strategy, random hiding strategy, and energy shrink strategy.…”
Section: Feature Selection Using Iaro Algorithmmentioning
confidence: 99%
“…Ma et al [13] proposed an identification method based on singular value decomposition (SVD) and MPSO-SVM. Cao et al [14] suggested an improved artificial bee colony optimization algorithm (IARO) with adaptive weight adjustment. IARO optimized support vector machine (SVM) to create an identification model to classify and identify vibration signals in different stages.…”
Section: Introductionmentioning
confidence: 99%